The Effect of Water Pipe Tobacco on the Kidney: A Narrative Review - Futuhi, Farzaneh; Abniki, Malihe; shahbazi, Vahideh (Novelty in Biomedicine, 2026)
Background: Water pipe tobacco is one of the methods of smoking that has a high prevalence worldwide, especially in Iran. Since tobacco can affect various body systems, in this study, we decided to review the effect of water pipe tobacco smoking on the kidneys. Materials and Methods: In this review study, previous studies on the effect of water pipe tobacco on the kidney were reviewed. The time period studied was from 2015 to 2025. Keywords of "Smoking Water Pipe”, "Smoking Water", "Water Pipe Tobacco", Tobacco, "Chronic Renal Disease”, "Chronic Kidney Disease", and "Kidney" were searched in PUBMED, EMBASE, and ELSEVIER databases. Results: Four studies were reviewed, and all were conducted on mice. According to studies, water pipe tobacco smoking causes various effects on the kidney through various mechanisms such as oxidative stress, decreased Superoxide dismutase, catalase, glutathione peroxidase activity, increased TBARS levels, lipid peroxidation, increased IL-6 and IL-1β, and DNA damage, including destruction of glomerular capillary endothelial cells, vacuolar destruction of proximal convoluted tubules, increased creatinine, blood urea nitrogen, and proteinuria. Conclusion: Water pipe tobacco smoking may cause kidney damage, but since no study has been conducted on humans so far, it is recommended that studies be conducted on human populations.